Experimental and numerical assessment of aerospace grade composites based on high-velocity impact experiments. (15th November 2018) - Wagner, Tim; Heimbs, Sebastian; Franke, Florian; Burger, Uli; Middendorf, Peter
Abstract: The experimental and numerical assessment of different aerospace grade composite materials under high-velocity impact is treated in this study. Characterisation of the materials, including thermosets (epoxy) and thermoplastics (PEEK) with carbon (unidirectional and woven fabric) and glass fibres, was conducted using high-velocity impact experiments. The test results indicate the glass fibre composites' superiority in the domain of classical composites in terms of weight-specific impact performance. The different carbon fibre composites have very similar ballistic limits but differ in terms of delamination behaviour. Subsequently, materials models are developed which reproduce interlaminar failure through the usage of surface-based cohesive contact formulations. By these means efficient and reliable simulation methods for impact events are developed.